Methodological and practical aspects of the harmonization of innovativeprocesses in Russian small business sector - Doroshenko, Yuri Anatolievich; Somina, Irina Vladimirovna (Serbian Journal of Management, 2016)
Abstract. An increase of innovative activity of small enterprises is included in the list of main directions of The Strategy of small and medium business development of Russian Federation for the period up to 2030. In the relevant sector of the economy the effectiveness of innovation is determined by the degree of its harmony. The work reflects the conceptual provisions of the harmonization of innovation processes in the internal and external environment in which small enterprises operate: the goal, objectives, object, principles and methods of harmonization are formulated as well. The harmonious relationships of innovation activity of small business are described by the dynamic model, in which indicators are ranked and subordinated to each other. The results of the practical approbation of the proposed methodology by types of economic activities are shown in the article. Keywords: innovation, harmonization, small enterprise, method of the dynamic standard, types of economic activity.